The first description of CTNNB1 syndrome in the Tunisian population: clinical investigation, molecular docking and molecular dynamics simulation of β-catenin/E-cadherin complex - Marwa Kharrat; Wafa bouchaala; Magdy M. D. Mohammed; Abir ben issa; Faiza Fakhfakh; Fatma kamoun; Chahnez Triki (Molecular Biology Reports, 2026)

AI-Assisted Simulation and Design of Sustained Release Metformin Tablets: Experimental Validation and Predictive Accuracy Assessment - Muthanna Abdulkarim; Abdullah B. Alabdulwahab; Arwa Alhaj Issa; Gamal M. Mahrous; Adel F. Alghaith; Sally Almanasra; Khaled Suwais (Journal of Pharmaceutical Innovation, 2026)

Melt-Extruded Paclitaxel Nanocrystal-Loaded Sutures for Sustained Local Drug Delivery - Hala M. Abdelhakk; Alhassan Issa; Crystal S. Shin; Feng Zhang (Pharmaceutical Research, 2026)

Does artificial intelligence reduce carbon emissions in OECD and BRICS? Examining the role of research and development - Issa Hamadou; Teguh Yudo Wicaksono; M. Luthfi Hamidi (Journal of Environmental Management, 2026)

The possible role of lycopene on the cerebellum of albino rat prenatally exposed to valproic acid: Animal model of autism spectrum disorder - Lubna T. Eid; Mostafa M. El-Habeby; Noha M. Issa; Nermeen M. Nooreldien (Tissue and Cell, 2025)

Metformin-loaded Chitosan nanoparticles alleviate insulin resistance in the polycystic ovarian syndrome rat model through modulation of PI3K/AKT/ GLUT4 in ovarian tissue - Samah Magdy Issa; Eman H. Thabet; Abeer.E. Dief; Walaa Omar; Samar R. Saleh; Marwa M. Essawy; Eman El Eter (Reproductive Biology, 2025)

Is mechanized conservation agriculture a promising solution for smallholder farmers? Evaluating its short-term agronomic and economic performance in Ethiopia - Bisrat G. Awoke; Thomas Daum; Karlheinz Köller; Dereje A. Anawte; Mubarek M. Issa; Teshome B. Gutema; Debele D. Enki; Godfrey Omulo; Regina Birner (Field Crops Research, 2025)

Enhancement of genetic gain for early seedling vigor traits through marker-assisted pedigree selection in rice (Oryza sativa L.) - Sudhamani Kalluru; Issa Keerthi; Madhavilatha Kommana; D. M. Withanawasam; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh; Lakshminarayana R. Vemireddy (Physiology and Molecular Biology of Plants, 2025)

Development of Bacillus spp for controlling wilt disease and improving the growth of tomato - Najeeb M. Almasoudi; Nashwa M. A. Sallam; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Fayez Althobaiti; Mohamed Housny; Hanan AlOmari; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2025)

Managing anthracnose fruit rot disease in pepper caused by Colletotrichum capsici via potash alum and frankincense essential oil - Mansour M. El-Fawy; Muhammad Imran; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Rabee A. Emam; Mohamed F. Abd El-Mageed; Najeeb M. Almasoudi; Nashwa M. A. Sallam; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2025)

Regulating microsomal triglyceride transfer protein with natural products for the treatment of hyperlipidaemia - Miral O. Sabry; Mohamed S. Sedeek; Sawsan M. El-Sonbaty; Marwa Y. Issa; Soheir M. El Zalabani (Natural Product Research, 2025)

Hybrid retrofitting for upgrading the seismic performance of adjacent bridges vulnerable to different damage modes including pounding - Jumana Hasina; Aman Mwafy; Anas Issa; M. Shahria Alam (Engineering Structures, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Comparative analysis of SDGs implementation: Testing a novel assessment framework approach - L. Issa; M. El-Fadel (Environmental Impact Assessment Review, 2025)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Selective apoptotic and genotoxic effects of pomegranate peel extract against human hepatocellular carcinoma HepG2 cell line - Wesam T. Basal; Medhat El-Sakka; Neima K. El-Sonousy; Aliaa M. Issa (Advances in Traditional Medicine, 2024)

First report of rust disease caused by Puccinia Porri on Egyptian leek in Egypt and its control by bergamot essential oil - Kamal A. M. Abo-Elyousr; Najeeb M. Almasoudi; Mansour M. El-Fawy; Ayman S. Saeed; Sameh H. E. Hamada; Esmat F. Ali; Ahmed A. Issa; Fayez Althobaiti; Ehab E. E. Korrat (Journal of Plant Pathology, 2024)

Clinical and Molecular Profiles of a Cohort of Egyptian Patients with Collagen VI-Related Dystrophy - Wessam E. Sharaf-Eldin; Karima Rafat; Mahmoud Y. Issa; Hasnaa M. Elbendary; Noura R. Eissa; Bahaa Hawaary; Nagwa E. A. Gaboon; Reza Maroofian; Joseph G. Gleeson; Mona L. Essawi; Maha S. Zaki (Journal of Molecular Neuroscience, 2024)
Collagen VI-related dystrophies (COL6-RD) display a wide spectrum of disease severity and genetic variability ranging from mild Bethlem myopathy (BM) to severe Ullrich congenital muscular dystrophy (UCMD) and the intermediate severities in between with dual modes of inheritance, dominant and recessive. In the current study, next-generation sequencing demonstrated potential variants in the genes coding for the three alpha chains of collagen VI ( COL6A1 , COL6A2 , or COL6A3 ) in a cohort of Egyptian patients with progressive muscle weakness ( n = 23). Based on the age of disease onset and the patient clinical course, subjects were diagnosed as follows: 12 with UCMD, 8 with BM, and 3 with intermediate disease form. Fourteen pathogenic variants, including 5 novel alterations, were reported in the enrolled subjects. They included 3 missense, 3 frameshift, and 6 splicing variants in 4, 3, and 6 families, respectively. In addition, a nonsense variant in a single family and an inframe variant in 3 different families were also detected. Recessive and dominant modes of inheritance were recorded in 9 and 8 families, respectively. According to ACMG guidelines, variants were classified as pathogenic ( n = 7), likely pathogenic ( n = 4), or VUS ( n = 3) with significant pathogenic potential. To our knowledge, the study provided the first report of the clinical and genetic findings of a cohort of Egyptian patients with collagen VI deficiency. Inter- and intra-familial clinical variability was evident among the study cohort.

Unveiling the Sensitivity Analysis of Port Carbon Footprint via Power Alternative Scenarios: A Deep Dive into the Valencia Port Case Study - Seyed Behbood Issa-Zadeh; M. Dolores Esteban; José-Santos López-Gutiérrez; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2024)
The Port of Valencia, a prominent maritime center, is actively working towards minimizing its carbon emissions and aims to become a completely carbon-neutral port soon. This research uses data-driven sensitivity analysis to explore realistic power-generating options for a seaport to reduce its emissions. This approach comprises changing key parameters in power consumption and deploying renewable energies (rather than electricity and infrastructure prices, which are beyond the scope of this study) to assess their impact on the port’s overall emissions profile. Through sensitivity analysis, policymakers and managers discover each scenario’s efficacy and find the best decarbonization strategies. After thoroughly examining four realistic scenarios, our research findings show that each scenario’s emission reduction share and sensitivity are practical and feasible. It becomes clear that gradually replacing traditional fossil fuels for electricity generation with renewables is a reasonable and realistic option for emissions reduction. The results demonstrate that focusing on reasonable targets, such as replacing 30% and 50% of electricity generation with renewables, is more achievable and beneficial in the medium term than ambitious goals, like replacing all electricity with renewable energy. This research contributes to reducing emissions of the Port of Valencia by using data-driven sensitivity analysis to find practical renewable energy strategies. It provides actionable insights for managers and policymakers to implement feasible decarbonization plans, emphasizing gradual adoption of renewables over ambitious goals, thus supporting sustainable maritime operations.

The mollifying effect of Sambucus nigra extract on StAR gene expression, oxidative stress, and apoptosis induced by fenpropathrin in male rats - Marsail S. Nashed; Eman I. Hassanen; Marwa Y. Issa; Adel F. Tohamy; Abdelbary M. Prince; Ahmed M. Hussien; Maher M. Soliman (Food and Chemical Toxicology, 2024)

Biodegradation of petroleum hydrocarbons using a novel bacterial strain isolated from hydrocarbons contaminated soil of Saudi Arabia - Mohammad Hazaimeh; Belal Muneeb Kanaan; Faleh A. AlFaleh; Mahmoud M. Elhaig; Emran Issa Khamaiseh; Qamar Zia; Mohammed Alaidarous; Chandra Shekhar Seth; Noorah Alsowayeh; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

An atypical expression of core α-Dystroglycan and Laminin-α2 in skin fibroblasts of patients with congenital muscular dystrophies - Sahar Sabry; Mahmoud Y Issa; Mohamed S Abdel-Hamid; Noura R Eissa; Sherif F Abdel-Ghafar; Mona M Ibrahim; Maha S Zaki (Molecular Biology Reports, 2023)
Background Congenital muscular dystrophies (CMDs) result from genetically inherited defects in the biosynthesis and/or the posttranslational modification (glycosylation) of laminin-α2 and α-dystroglycan (α-DG), respectively. The interaction between both proteins is responsible for the stability and integrity of the muscle cell. We aimed to study the expression profiles of both proteins in two classes of CMDs. Subjects and methods Whole-exome sequencing (WES) was done for four patients with neuromuscular manifestations. The expression of core α-DG and laminin-α2 subunit in skin fibroblasts and MCF-7 cells was assessed by western blot. Results WES revealed two cases with nonsense mutations; c.2938G > T and c.4348 C > T, in LAMA2 encodes laminin-α2. It revealed also two cases with mutations in POMGNT1 encode protein O-mannose beta-1,2-N-acetylglucosaminyltransferase mutations. One patient had a missense mutation c.1325G > A, and the other had a synonymous variant c.636 C > T. Immunodetection of core α-DG in skin fibroblasts revealed the expression of truncated forms of core α-DG accompanied by reduced expression of laminin-α2 in POMGNT1-CMD patients and one patient with LAMA2-CMD. One patient with LAMA2-CMD had overexpression of laminin-α2 and expression of a low level of an abnormal form of increased molecular weight core α-DG. MCF-7 cells showed truncated forms of core α-CDG with an absent laminin-α2. Conclusion A correlation between the expression pattern/level of core α-DG and laminin-α2 could be found in patients with different types of CMD.

Intermuscular Coherence in Spinocerebellar Ataxias 3 and 6: a Preliminary Study - Naoum P. Issa; Serdar Aydin; Shail Bhatnagar; Nicholas W. Baumgartner; Jacquelyn Hill; Sravya Aluri; Chloe S. Valentic; Eric Polley; Christopher M. Gomez; Kourosh Rezania (The Cerebellum, 2023)
Spinocerebellar ataxias (SCAs) are familial neurodegenerative diseases involving the cerebellum and spinocerebellar tracts. While there is variable involvement of corticospinal tracts (CST), dorsal root ganglia, and motor neurons in SCA3, SCA6 is characterized by a pure, late-onset ataxia. Abnormal intermuscular coherence in the beta-gamma frequency range (IMCβγ) implies a lack of integrity of CST or the afferent input from the acting muscles. We test the hypothesis that IMCβγ has the potential to be a biomarker of disease activity in SCA3 but not SCA6. Intermuscular coherence between biceps brachii and brachioradialis muscles was measured from surface EMG waveforms in SCA3 ( N = 16) and SCA6 ( N = 20) patients and in neurotypical subjects ( N = 23). IMC peak frequencies were present in the β range in SCA patients and in the γ range in neurotypical subjects. The difference between IMC amplitudes in the γ and β ranges was significant when comparing neurotypical control subjects to SCA3 ( p < 0.01) and SCA6 ( p = 0.01) patients. IMCβγ amplitude was smaller in SCA3 patients compared to neurotypical subjects ( p < 0.05), but not different between SCA3 and SCA6 patients or between SCA6 and neurotypical subjects. IMC metrics can differentiate SCA patients from normal controls.

Lasiodiplodia species associated with mango (Mangifera indica L.) decline in Burkina Faso and influence of climatic factors on the disease distribution - Oumarou Zoéyandé Dianda; Issa Wonni; Léonard Ouédraogo; Philippe Sankara; Charlotte Tollenaere; Emerson M. Del Ponte; Diana Fernandez (Physiological and Molecular Plant Pathology, 2023)

High multidrug resistance of Listeria monocytogenes and association with water sources in sheep and goat dairy flocks in Jordan - Mohammad M. Obaidat; Issa A. AlShehabat (Preventive Veterinary Medicine, 2023)

Seismic response evaluation of spring-based piston braced frames by employing closed-loop dynamic (CLD) testing - Anas Issa; Navid Rahgozar; M. Shahria Alam (Engineering Structures, 2023)

A Framework for Accurate Carbon Footprint Calculation in Seaports: Methodology Proposal - Seyed Behbood Issa Zadeh; José Santos López Gutiérrez; M. Dolores Esteban; Gonzalo Fernández-Sánchez; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2023)
According to the 2020 European Sea Ports Organization Environmental Report, ports are the second biggest environmental concern for climate change due to greenhouse gas emissions. Furthermore, the International Association of Ports and Harbors determined that seaports are carbon-intensive and environmentally harmful because of increased commercial and non-commercial activities surrounding them. Due to the urgent concern to address solutions in this research line, this study aims to present a frame of reference to estimate the Carbon Footprint in ports through an innovative method. The study design presents a Meta-Analyses Scoping Review based on the PRISMA-ScR methodology to analyse the current articles, normativity and primary resources related to the Carbon Footprint estimation approach in seaports. Then, a categorization for the new method of Carbon Footprint and scopes description calculation is presented. Besides, the Port of Valencia, a famous Spanish port, provides the case study to apply and confirm the approach. Findings state that this new approach, with the designation of new boundaries and factors affecting ports’ emissions would lead to an accurate estimation of the carbon footprint of ports. The originality and value of this work-study deliver scientific interpretations, reflections, and suggestions for future research and validation.

Experimental investigation and seismic analysis of a novel self-centering piston-based bracing archetype with polyurethane cores - Anas Issa; Navid Rahgozar; M. Shahria Alam (Engineering Structures, 2023)

Characterization of Seismic Source Zones in the Gulf of Aden Region - Ahmed Deif; Harith Al Kubaisy; Iman Farag Abu El-Nader; Issa El-Hussain; Yousuf Al-Shijbi; Adel M. E. Mohamed (Pure and Applied Geophysics, 2023)

Late Pleistocene travertine deposits in the Jordan Valley—Dead Sea area: lithofacies, sedimentological properties and depositional environments - Issa M. Makhlouf; Khalil M. Ibrahim; Ali R. El Naqah; Sana’ M. Al-Thawabteh (Arabian Journal of Geosciences, 2023)

The role of ivabradine in doxorubicin-induced cardiotoxicity: exploring of underlying argument - Hayder M. Al-kuraishy; Hajer K. Issa; Ali I. Al-Gareeb; Maisra M. El-Bouseary; Amal Youssef; Ahmed Shaban Abdelaziz; Hesham Ahmed Khalifa; Gaber El-Saber Batiha (Inflammopharmacology, 2022)

Ecofriendly adsorption and sensitive detection of Hg (II) by biomass-derived nitrogen-doped carbon dots: process modelling using central composite design - Mohammed Abdullah Issa; Hamid Zentou; Zaid H. Jabbar; Zurina Z. Abidin; Haninah Harun; Noor Amirah Abdul Halim; Mohammed M. Alkhabet; Musa Y. Pudza (Environmental Science and Pollution Research, 2022)

Potential of ( Citrus nobilis Lour × Citrus deliciosa Tenora) metabolites on COVID-19 virus main protease supported by in silico analysis - Seham S. El-Hawary; Marwa Y. Issa; Hanaa S. Ebrahim; Anber F. Mohammed; Alaa M. Hayallah; Essam M. Abd El-Kadder; Ahmed. M. Sayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

ICP-MS determination of elemental abundance in traditional medicinal plants commonly used in the Kingdom of Saudi Arabia - Rizwan Ahmad; Heba Shaaban; Sahar Y. Issa; Anwar Alsaad; Majd Alghamdi; Njoud Hamid; Rand Osama; Sara Algarni; Ahmed Mostafa; Abdulmalik M. Alqarni; Mohammed Aldholmi; Muhammad Riaz (Food Additives & Contaminants Part B-Surveillance, 2022)

Beat the stress: breeding for climate resilience in maize for the tropical rainfed environments - Boddupalli M. Prasanna; Jill E. Cairns; P. H. Zaidi; Yoseph Beyene; Dan Makumbi; Manje Gowda; Cosmos Magorokosho; Mainassara Zaman-Allah; Mike Olsen; Aparna Das; Mosisa Worku; James Gethi; et al. (Theoretical and Applied Genetics, 2021)
Key message Intensive public sector breeding efforts and public-private partnerships have led to the increase in genetic gains, and deployment of elite climate-resilient maize cultivars for the stress-prone environments in the tropics. Abstract Maize ( Zea mays L.) plays a critical role in ensuring food and nutritional security, and livelihoods of millions of resource-constrained smallholders. However, maize yields in the tropical rainfed environments are now increasingly vulnerable to various climate-induced stresses, especially drought, heat, waterlogging, salinity, cold, diseases, and insect pests, which often come in combinations to severely impact maize crops. The International Maize and Wheat Improvement Center (CIMMYT), in partnership with several public and private sector institutions, has been intensively engaged over the last four decades in breeding elite tropical maize germplasm with tolerance to key abiotic and biotic stresses, using an extensive managed stress screening network and on-farm testing system. This has led to the successful development and deployment of an array of elite stress-tolerant maize cultivars across sub-Saharan Africa, Asia, and Latin America. Further increasing genetic gains in the tropical maize breeding programs demands judicious integration of doubled haploidy, high-throughput and precise phenotyping, genomics-assisted breeding, breeding data management, and more effective decision support tools. Multi-institutional efforts, especially public–private alliances, are key to ensure that the improved maize varieties effectively reach the climate-vulnerable farming communities in the tropics, including accelerated replacement of old/obsolete varieties.

Improved lithospheric attenuation structure of the Arabian Peninsula through the use of national network data - Michael E. Pasyanos; Yahya M. Tarabulsi; Salah Y. Al-Hadidy; Wael W. Raddadi; Abdullah D. Mousa; Issa El-Hussain; Farah Al-Jeri; Haydar Al-Shukri; Rengin Gök (Arabian Journal of Geosciences, 2021)

Site-specific deterministic and probabilistic tsunami hazard assessment for Diba-Oman and Diba-Al-Emirates - Issa El-Hussain; Zaid Al-Habsi; Khalid Al Bloushi; Rachid Omira; Ahmed Deif; Maria Ana Baptista; Adel M. E. Mohamad (Arabian Journal of Geosciences, 2021)

Exploratory Study on Lercanidipine Hydrochloride Polymorphism: pH-Dependent Solubility Behavior and Simulation of its Impact on Pharmacokinetics - Ilia Alekseevich Repin; Raimar Loebenberg; John DiBella; António C. L. Conceição; Manuel E. Minas da Piedade; Humberto G. Ferraz; Michele G. Issa; Nadia A. Bou-Chacra; Catharine F. M. Ermida; Gabriel L. B. de Araujo (AAPS PharmSciTech, 2021)

Discovery of genomic regions and candidate genes for grain weight employing next generation sequencing based QTL-seq approach in rice (Oryza sativa L.) - Reddyyamini Bommisetty; Navajeet Chakravartty; Reddaiah Bodanapu; Jeevula B. Naik; Sanjib K. Panda; Sivarama P. Lekkala; Krishna Lalam; George Thomas; S. J. Mallikarjuna; G. R. Eswar; Gopalakrishna M. Kadambari; Swarajyalakshmi N. Bollineni; et al. (Molecular Biology Reports, 2020)

Myocardial adaptability in young and older-aged sea-level habitants sojourning at Mt Kilimanjaro: are cardiac compensatory limits reached in older trekkers? - Glenn M. Stewart; Courtney M. Wheatley-Guy; Norman R. Morris; Kirsten E. Coffman; Jan Stepanek; Alex R. Carlson; Amine Issa; Michael A. Schmidt; Bruce D. Johnson (European Journal of Applied Physiology, 2020)

Deaggregation of probabilistic seismic hazard for selected cities in the Arabian Peninsula - Yousuf Al-Shijbi; Ahmed Deif; Issa El-Hussain; Adel M. E. Mohamed; Amna Al-Dairi (Arabian Journal of Geosciences, 2019)

Biological control of damping-off of tomato caused by Pythium aphanidermatum by using native antagonistic rhizobacteria isolated from Omani soil - Hanan S. Al-Hussini; Amna Y. Al-Rawahi; Abdullah A. Al-Marhoon; Shurooq A. Al-Abri; Issa H. Al-Mahmooli; Abdullah M. Al-Sadi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2019)

Effect of recycled glass powder on properties of cementitious materials contains styrene butadiene rubber - Asmahan Issa Jubeh; Doha M. Al Saffar; Bassam A. Tayeh (Arabian Journal of Geosciences, 2019)

Naringenin mitigates titanium dioxide (TiO2)-induced chronic arthritis in mice: role of oxidative stress, cytokines, and NFκB - Marília F. Manchope; Nayara A. Artero; Victor Fattori; Sandra S. Mizokami; Dimitrius L. Pitol; João P. M. Issa; Sandra Y. Fukada; Thiago M. Cunha; José C. Alves-Filho; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

In Vitro Comparative Evaluation of Antioxidant Activity of Hydrophobic and Hydrophilic Extracts from Algicolous Fungi - Awatief F. Hifney; Mustafa A. Fawzy; Khayria M. Abdel-Gawad; Ahmed A. Issa; Mohamed Gomaa (Journal of Aquatic Food Product Technology, 2017)

Intraseasonal variability of low-level moisture transport over West Africa - M. Issa Lélé; Lance M. Leslie (Climate Dynamics, 2016)

Biodegradation of Palisada perforata (Rhodophyceae) and Sargassum sp. (Phaeophyceae) biomass by crude enzyme preparations from algicolous fungi - Mohamed Gomaa; Awatief F. Hifney; Mustafa A. Fawzy; Ahmed A. Issa; Khayria M. Abdel-Gawad (Journal of Applied Phycology, 2015)

Spatio-temporal, environmental factors, and host identity shape culturable-epibiotic fungi of seaweeds in the Red Sea, Egypt - Khayria M. Abdel-Gawad; Awatief F. Hifney; Ahmed A. Issa; Mohamed Gomaa (Hydrobiologia, 2014)

Analysing the relationship between land units and plant communities: The case of Socotra Island (Yemen) - F. Attorre; A. Issa; L. Malatesta; A. Adeeb; M. De Sanctis; M. Vitale; A. Farcomeni (Plant Biosystems, 2014)

Inhibition of pancreatic lipase by berberine and dihydroberberine: an investigation by docking simulation and experimental validation - Mohammad Mohammad; Ihab M. Al-masri; Ala Issa; Ayman Khdair; Yasser Bustanji (Medicinal Chemistry Research, 2013)

Multiple source imagery and linear features for detection of urban expansion in Aqaba City, Jordan - Rami Issa Al-Ruzouq; Abdallah Al-Zoubi; Emad E. Akawi; Abdalrahman A. Abueladas; Tina M. Niemi (International Journal of Remote Sensing, 2012)

Bacterial diversity of periodontal and implant-related sites detected by the DNA Checkerboard method - C. Nascimento; N. Monesi; I. Y. Ito; J. P. M. Issa; R. F. Albuquerque Junior (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Synthesis of new series of pyrazolo[4,3-d]pyrimidin-7-ones and pyrido[2,3-d]pyrimidin-4-ones for their bacterial and cyclin-dependent kinases (CDKs) inhibitory activities - Detlef Geffken; Raafat Soliman; Farid S. G. Soliman; Magdi M. Abdel-Khalek; Doaa A. E. Issa (Medicinal Chemistry Research, 2011)

Extraction of Co, Ni, Cu, Zn and Cd ions using 2-aminophenylaminopropylpolysiloxane - Nizam M. El-Ashgar; Issa M. El-Nahhal; Mohamed M. Chehimi; Florence Babonneau; Jacques Livage (Environmental Chemistry Letters, 2010)

Boronated phosphonium salts containing arylboronic acid, closo-carborane, or nido-carborane: synthesis, X-ray diffraction, in vitro cytotoxicity, and cellular uptake - Daniel E. Morrison; Fatiah Issa; Mohan Bhadbhade; Ludwig Groebler; Paul K. Witting; Michael Kassiou; Peter J. Rutledge; Louis M. Rendina (JBIC Journal of Biological Inorganic Chemistry, 2010)

Nostoc cyanobacterial inoculation in South African agricultural soils enhances soil structure, fertility, and maize growth - M. P. Maqubela; P. N. S. Mnkeni; O. Malam Issa; M. T. Pardo; L. P. D’Acqui (Plant and Soil, 2009)

Parasite Prevalence, Abundance, and Diversity in a Semi-free-ranging Colony of Mandrillus sphinx - Joanna M. Setchell; Issa-Ben Bedjabaga; Benoit Goossens; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (International Journal of Primatology, 2007)

A novel gene for Usher syndrome type 2: mutations in the long isoform of whirlin are associated with retinitis pigmentosa and sensorineural hearing loss - Inga Ebermann; Hendrik P. N. Scholl; Peter Charbel Issa; Elvir Becirovic; Jürgen Lamprecht; Bernhard Jurklies; José M. Millán; Elena Aller; Diana Mitter; Hanno Bolz (Human Genetics, 2007)

Secondary sexual characters and female quality in primates - Joanna M. Setchell; Marie J. E. Charpentier; Issa-Ben Bedjabaga; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (Behavioral Ecology and Sociobiology, 2006)

Artificial Insemination Using Local Cattle Breeds in Niger - F. Cristofori; M. Issa; A. Yenikoye; G. Trucchi; G. Quaranta; M. Chanono; C. Semita; H. Marichatou; M. Mattoni (Tropical Animal Health and Production, 2005)

A methodological study on participatory barley breeding II. Response to selection - S. Ceccarelli; S. Grando; M. Singh; M. Michael; A. Shikho; M. Al Issa; A. Al Saleh; G. Kaleonjy; S.M. Al Ghanem; A.L. Al Hasan; H. Dalla; S. Basha; et al. (Euphytica, 2003)

Effect of manganese and calcium deficiency on the growth and oxygen exchange ofScenedesmus intermedius cultured for successive generations - M. S. Adam; A. A. Issa (Folia Microbiologica, 2000)

Influence of selenium on toxicity of some heavy metals in the green algaScenedesmus obliquus - A. A. Issa; M. S. Adam (Folia Microbiologica, 1999)

An Evaluation of Insecticide-Impregnated Screens against Glossina Austeni (Diptera: Glossinidae) on Unguja Island of Zanzibar - Marc J. B. Vreysen; Khalfan M. Saleh; Issa S. Khamis; Furaha Mramba (International Journal of Tropical Insect Science, 1999)

Molecular mechanism of vitamin D receptor action - L. L. Issa; G. M. Leong; J. A. Eisman (Inflammation Research, 1998)

Effect of Ca2+ on the detoxification of Cd2+ byScenedesmus obliquus cells at low or high temperature - A. A. Issa; M. S. Adam; R. Abdel-Basset (Folia Microbiologica, 1998)